2023
DOI: 10.1002/ppsc.202200167
|View full text |Cite
|
Sign up to set email alerts
|

Topotactical Route to Multiwalled Cerium Oxide Nanotubes from MWCNTs

Abstract: biomedicine due to its ability to shift easily between Ce 4+ /Ce 3+ oxidation states, high oxygen storage capacity (OSC), increased oxygen ion conductivity, and excellent biocompatibility. [1,2] Over the years, extensive research efforts have been made to develop the controllable synthesis of CeO 2 nanomaterials with diverse structural morphologies owing to the importance of nano-size and geometrical effects. [3,4] Due to their inherent hollow structure, CeO 2 nanotubes possess a high surfaceto-volume ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the intensities of the first-shell and higher-shell peaks increased with the CeO x contents, implying larger CeO x NPs. The weak long-range order for CeO x /CNT(0.4), combined with XPS and XANES results, suggested that CeO x /CNT(0.4) mainly consisted of atomically dispersed Ce 3+ –O x species . These spectroscopic results suggest a possible pathway for CeO x growth on the CNT.…”
Section: Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the intensities of the first-shell and higher-shell peaks increased with the CeO x contents, implying larger CeO x NPs. The weak long-range order for CeO x /CNT(0.4), combined with XPS and XANES results, suggested that CeO x /CNT(0.4) mainly consisted of atomically dispersed Ce 3+ –O x species . These spectroscopic results suggest a possible pathway for CeO x growth on the CNT.…”
Section: Results and Discussionmentioning
confidence: 97%
“…The weak longrange order for CeO x /CNT(0.4), combined with XPS and XANES results, suggested that CeO x /CNT(0.4) mainly consisted of atomically dispersed Ce 3+ −O x species. 54 These spectroscopic results suggest a possible pathway for CeO x growth on the CNT. The Ce 3+ precursor ions first attach to surface oxygenate species on the CNT.…”
Section: ■ Introductionmentioning
confidence: 84%